If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(n + -10) = 4(n + -5) Reorder the terms: 2(-10 + n) = 4(n + -5) (-10 * 2 + n * 2) = 4(n + -5) (-20 + 2n) = 4(n + -5) Reorder the terms: -20 + 2n = 4(-5 + n) -20 + 2n = (-5 * 4 + n * 4) -20 + 2n = (-20 + 4n) Add '20' to each side of the equation. -20 + 20 + 2n = -20 + 20 + 4n Combine like terms: -20 + 20 = 0 0 + 2n = -20 + 20 + 4n 2n = -20 + 20 + 4n Combine like terms: -20 + 20 = 0 2n = 0 + 4n 2n = 4n Solving 2n = 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. 2n + -4n = 4n + -4n Combine like terms: 2n + -4n = -2n -2n = 4n + -4n Combine like terms: 4n + -4n = 0 -2n = 0 Divide each side by '-2'. n = 0 Simplifying n = 0
| 2x+y+3=30 | | 1-x=5(-7+7x) | | 23=v+7 | | 100[0.02(x+4)]= | | 3x-3x-3=12 | | r=st+p | | 5x+3(6x+18)=174 | | -2x+10=-14+4x | | 125x+5x=125 | | -4-(2-3p)= | | 45+a=72 | | 7x+3(3x-10)=162 | | 125+5x=125+10x | | 45+a=75 | | 27+3x=66 | | c+5=25 | | 18x^2-120x-858=0 | | -17+2n=-3(6n+4)-5 | | 4+3x=3(6x-3)-8 | | y=0.6x+5.35 | | 7b-5(-8-7b)=-1+b | | x+4=-26+6x | | -6.4(6t+6)-1.4(3t-5)= | | 5w=2(2w+4)+10 | | 18x^2+37x-20=0 | | 72x=16 | | -34-4m=-1 | | 5x+4+6x-4=180 | | 3(x-8)=4x+4 | | -2(m-1)=-6-2m | | 10y-2x=0 | | -3x+5=5x+5 |